2019
DOI: 10.7124/bc.000a0f
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity evaluation of thieno[3,2-e][1,2,3]triazolo[1,5-a]pyrimidines and thieno[2,3-e][1,2,3]triazolo[1,5-a]pyrimidine derivatives

Abstract: In vitro evaluation of anticancer activity of synthesized thieno[3,2-e][1,2,3]triazolo[1,5-a] pyrimidines and thieno[2,3-e][1,2,3]triazolo[1,5-a] pyrimidines. Methods. Organic synthesis, in vitro cytotoxicity assay, MTT assay, spectrophotometry, statistical analysis. Results. The isomeric thienotriazolopyrimidines synthesized were tested for their anticancer activity in the NCI-60 cancer cell line panel, a group of 60 human cancer cell lines. The selective influence of 5-oxo-4,5,6,7,8,9-hexahydrobenzo[4,5]thie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…In our previous studies, new active compounds with a 1,2,3triazolyl-4-carboxamide motif were reported (Shyyka et al, 2019;Pokhodylo, Shyyka, Finiuk & Stoika, 2020;Pokhodylo, Slyvka & Pavlyuk, 2020). Additionally, 1,2,3-triazolyl-4carboxamide derivatives were found to be inhibitors of the Wnt/-catenin signalling pathway (Obianom et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 96%
“…In our previous studies, new active compounds with a 1,2,3triazolyl-4-carboxamide motif were reported (Shyyka et al, 2019;Pokhodylo, Shyyka, Finiuk & Stoika, 2020;Pokhodylo, Slyvka & Pavlyuk, 2020). Additionally, 1,2,3-triazolyl-4carboxamide derivatives were found to be inhibitors of the Wnt/-catenin signalling pathway (Obianom et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 96%
“…In our previous studies on the anticancer screening of various 1,2,3-triazoles, compounds based on 1,2,3-triazolyl-4carboxamide scaffolds possessed the highest antiproliferative activity (Shyyka et al, 2019;Pokhodylo et al, 2013Pokhodylo et al, , 2014. Furthermore, a series of 6,7-disubstituted-4-(2-fluorophenoxy)quinoline derivatives possessing the 1,2,3-triazole-4carboxamide moiety have been evaluated against c-Met kinase and five typical cancer cell lines (A549, H460, HT-29, MKN-45 and U87MG) and exhibited moderate to excellent ISSN 2056-9890 antiproliferative activity (Zhou et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 96%
“…У попередніх працях ми дослідили чимало доміно-реакцій за участі 1,3-диполярних азидів з утворенням різноманітних анельованих гетероциклічних систем, зокрема, [1,2,3]триазоло [1,5-a]піримідинів [10]. Серед цих речовин знайдено сполуки, що проявили протипухлинну активність [11].…”
Section: вступunclassified